Programmers' Capital. - Kiesewetter-Köbinger, Swen (Computer (00189162), 2010)
The article focuses on how computing professionals can protect their intellectual capital (IC). It explores the individual, microeconomic aspect of intellectual knowledge capital. The intellectual property protection laws are seldom challenged by opponents from the computing profession because their fundamental rights are frequently the ones most notoriously disregarded. The author proposes that patent protection should confine exceptions to the author's exclusive copyright.